2008
DOI: 10.1051/agro:2007031
|View full text |Cite
|
Sign up to set email alerts
|

Methodological progress in on-farm regional agronomic diagnosis. A review

Abstract: The development of sustainable cropping systems is a key priority for agronomists and crop scientists. A first step involves understanding the relationship between cropping system performance and farmers' practices. To complete this step, a methodological framework entitled Regional Agronomic Diagnosis (RAD) has been developed. During the last ten years, the scope of the regional agronomic diagnosis has been enlarged to include several factors describing crop quality and the environmental impact of cropping sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 72 publications
0
28
0
2
Order By: Relevance
“…These assessments may well be useful for planning strategies for yield improvement on the broad scale but potentially less relevant at the farm level unless followed up by local diagnosis of limiting factors (Dore et al 1997(Dore et al , 2008Siddique et al 2012. The potential errors associated with such methods have been outlined by Neumann et al (2010).…”
Section: Estimation Of Potential Grain Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…These assessments may well be useful for planning strategies for yield improvement on the broad scale but potentially less relevant at the farm level unless followed up by local diagnosis of limiting factors (Dore et al 1997(Dore et al , 2008Siddique et al 2012. The potential errors associated with such methods have been outlined by Neumann et al (2010).…”
Section: Estimation Of Potential Grain Yieldmentioning
confidence: 99%
“…This gives farmers some scope to adjust management according to seasonal conditions and available resources. Identifying the factors most likely to be limiting in any particular paddock by objective means (diagnostic research as reported in Dore et al 1997Dore et al , 2008Anderson et al 2014;Sharma and Anderson 2014) suggests a hierarchy of practices that can be tested and applied according to available resources, perceived risk and farmer convenience. An example is given in Table 2 for two farm sites where both zero tillage and partial stubble retention were standard practices in mixed farming systems based on barley, canola, oats, pasture and grazing by sheep.…”
Section: Diagnosis Of Constraintsmentioning
confidence: 99%
“…Different "ecologically intensive" model design frameworks have thus been proposed (Malézieux 2012;Gaba et al 2015). However, existing multispecies systems-from which agronomists could be inspired-are much harder to assess than monospecies systems because of their inherent heterogeneity, hence the many difficulties to quantify interactions (Doré et al 2008;Malézieux et al 2008). This is the case especially for complex agroforestry systems in the humid tropics that have many potential advantages that could be tapped depending on the relationships and regulations between species in the agrosystem, i.e., a higher overall productivity per unit area, a better control of pest pressure, and increased environmental services such as biodiversity conservation, soil fertility, and carbon sequestration .…”
Section: Introductionmentioning
confidence: 99%
“…Our work, based on on-farm research, compares the relationship between crop management itinerary and yield (Loyce and Wery, 2006;Doré and Meynard, 2006;Doré et al, 2007), and gives greater insight into production logic than would a simple survey of practices. Our research showed that in the semi-arid region, there is a direct relationship between the diversity of farm management methods and crop management itineraries, based on both region and climate.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first steps is to understand the relationship between the agricultural performance of production systems and farming practices (Coleno and Duru, 2005;Doré et al, 2007). The evaluation of economic performance of production systems (with scarce data available in our context) must take into account the diverse crop management practices (Cochet and Devienne, 2006) and the variable access to production resources, for example the purchase or lease of plots from one year to other (Gérard et al, 2001).…”
Section: Introductionmentioning
confidence: 99%